Audiovisual Archives of Hellenism, Two Research Projects - Koutsopanagou, Gioula (Études helléniques / Hellenic Studies, 2000)
Over the last decade, interest in the preservation and exploitation of written archives, especially audiovisual archives, has grown. In fact AV archives have become the theme of many EU-subsidized projects. The poor condition of written and audiovisual archives in Greece recently led to the recognition of an urgent need to preserve the national heritage of Greece and its diaspora. Two research projects: Encyclopaedia of the Greek Press, 1784-1996 and the thematic proposal Mediterranean Diaspora: Visions of Multicultural and Multilingual Encounter through the Audiovisual Archives, which is part of the CapMed project for the preservation and exploitation of the Euro-Mediterranean audiovisual memory, focus on the audiovisual archives of Hellenism. These two projects are run by the Institute for Neohellenic Research/The National Hellenic Research Foundation (KNE/EIE) and the Hellenic Audiovisual Institute (IOM) of the Greek Ministry for the Press and Mass Media respectively.